Characterization of the mouse analogues of CD59 using novel monoclonal antibodies: tissue distribution and functional comparison - Harris, Claire L (Blackwell Science Inc, 2003)
CD59, the sole membrane regulator of the membrane attack complex of complement, is broadly and abundantly expressed in man and other mammals. In mouse, CD59 is encoded by two homologous genes. The expression patterns and functional roles of the proteins encoded by these genes, mCD59a and mCD59b, have not been well characterized. Here we describe the generation of monoclonal and polyclonal antibodies detecting specifically mCD59a and mCD59b. These reagents have been used to study function and to ascertain the cell and tissue distributions of mCD59a and mCD59b. mCD59a was broadly distributed on endothelia, erythrocytes, platelets, and on numerous other cell types in organs, a distribution pattern resembling that of CD59 in other species. In marked contrast, expression of mCD59b was restricted to germ cell elements in the testis and mature spermatozoa. Both mCD59a and CD59b inhibited human and rodent complement with similar efficiency. These findings demonstrate that the broadly distributed mCD59a is the key regulator of the terminal complement pathway in mice whereas CD59b, expressed only in testis and on sperm, probably plays other roles in vivo.